KINERJA PEMERINTAH TERHADAP PENGELOLAAN DANA DESA DI DESA LEPPANGENG KECAMATAN PITU RIASE - Jumariah; Ikbal, Muhammad; Hardianti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to determine and analyze how village government performance affects the management of village funds in Leppangeng Village, Pitu Riase District. This research is motivated by the existence of problems in the implementation of village fund management, such as late reporting, low community participation, and less than optimal utilization of funds for development and community empowerment. The method used in this research is descriptive quantitative method with data collection techniques through observation, questionnaires, and literature study. The number of samples in this study were 85 respondents, determined using the Slovin formula. The data collected was then processed and analyzed with the help of descriptive statistics using SPSS and a Likert scale.